Psychometric Properties of Language Assessments for Children Aged 4–12 Years: A Systematic Review - Denman, Deborah; Speyer, Renée; Munro, Natalie; Pearce, Wendy M.; Chen, Yu-Wei; Cordier, Reinie (Frontiers in Psychology, 2017)
Abstract Introduction: Standardized assessments are widely used by speech pathologists in clinical and research settings to evaluate the language abilities of school-aged children and inform decisions about diagnosis, eligibility for services and intervention. Given the significance of these decisions, it is important that assessments have sound psychometric properties. Objective: The aim of this systematic review was to examine the psychometric quality of currently available comprehensive language assessments for school-aged children and identify assessments with the best evidence for use. Methods: Using the PRISMA framework as a guideline, a search of five databases and a review of websites and textbooks was undertaken to identify language assessments and published material on the reliability and validity of these assessments. The methodological quality of selected studies was evaluated using the COSMIN taxonomy and checklist. Results: Fifteen assessments were evaluated. For most assessments evidence of hypothesis testing (convergent and discriminant validity) was identified; with a smaller number of assessments having some evidence of reliability and content validity. No assessments presented with evidence of structural validity, internal consistency or error measurement. Overall, all assessments were identified as having limitations with regards to evidence of psychometric quality. Conclusions: Further research is required to provide good evidence of psychometric quality for currently available language assessments. Of the assessments evaluated, the Assessment of Literacy and Language, the Clinical Evaluation of Language Fundamentals- 5th Edition, the Clinical Evaluation of Language Fundamentals – Preschool: 2nd Edition and the Preschool Language Scales – 5th Edition presented with most evidence and are thus recommended for use.